Paths for improvements of smallholder dairies: Case-study on local food security in arid regions of China. (December 2021) - Li, Shanshan; Bai, Yanfu; Jiao, Jianxin; Degen, A. Allan; Zhang, Tao; Wang, Wenyin; Ding, Luming; Long, Ruijun; Peng, Zhen; Dang, Zhiqiang; Zhang, Dawei; Shang, Zhanhuan
Abstract: The trend today leans towards urbanization and large farming enterprises. However, in 2019–2020, with the impact of the COVID-19 pandemic, the supply of commercial milk was disrupted, and the local smallholder dairy farmers played an important role in stabilizing food and nutritional security in rural, arid areas of China. The aim of this study was to describe and understand the operation of smallholder dairy farms and suggest what improvements are needed. We interviewed 45 smallholder dairy farmers from Gansu Province. A questionnaire was used to collect information on the dairy operation, including, number of cows, cow breeds, feed offered, milk yield and on management and open-ended discussions on the needs of the farmers to improve their dairies. Feed samples were collected at each farm to determine composition and milk samples were collected to analyze for composition and fatty acid content, and to compare the quality with commercial milk. Smallholder farmers generally fed dairy cows local, low-quality forages, mainly wheat straw and corn stover (CS/WS), and the milk yield was low, however, milk had a high content of beneficial unsaturated and polyunsaturated fatty acids. Milk from smallholder farms had lower concentrations of undesirable saturated fatty acids, higher concentrations of beneficial unsaturated and polyunsaturated fatty acids, and a lower atherogenic index than commercial milk. Proper sanitation measures and veterinary care were often lacking in these remote areas, leading to high somatic cell counts (SCC). A modified version of grounded theory was used to construct categories of what the farmers perceived was needed to improve their dairies. Four categories emerged in the following order: 1) equipment and management, 2) government support, 3) better cows, and 4) better feed. In a follow-up survey in 2020 of 18 farmers, conditions generally remained the same, including feed offered the animals, which would indicate that the milk composition remained the same. It was concluded that smallholder dairy farmers can provide food and nutritional security, especially for local residents in remote, rural, arid areas, but improvements in facilities, management, feed, cow breeds and sanitation are needed. Government subsidies should be implemented to help the smallholder dairy farmers. Results from this study provide information for local governments in their decision-making policies to stabilize smallholder dairies. Highlights: Smallholder dairies (ShD) in rural, arid areas in China feed cows low quality feed. Milk concentrations of UFA and PUFA from ShD was higher than in commercial milk. Atherogenic index from ShD was lower than in commercial milk. Sanitation and veterinary care need improvement in ShD. ShD can be important in stabilizing nutritional security in arid areas of China.